DAYA HAMBAT DARI EKSTRAK SARANG BURUNG WALET PADA PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS DAN PORPHYROMONAS GINGIVALIS - Utami, Ulfah; Putri, Megananda Hiranya; Nurjanah, Neneng; Eldarita, Eldarita (Poltekkes Kemenkes Bandung, 2024)
Type 2 diabetes (T2DM) is one of the fastest growing global diseases of the 21st century, with its prevalence more than tripling in the last 20 years and affecting 10.5% of the world's population aged 20-79 years. In Indonesia, diabetes mellitus among 20-79 year olds is 10.6%. The most widely cultivated type of swallow nest is Collocatia fuciphaga. Collocatia fuciphaga is a species of bird that produces nests from its white saliva. Swallow's nest contains sialic acid which is only produced from saliva, calcium, glycoproteins and Epidermal Growth Factor (EGF), one of the benefits of which is to accelerate wound healing. The study aimed to determine the inhibition of swallow's nest extract on the growth of Streptococcus mutans and Porphyromonas gingivalis bacteria. The swallow's nest extract test used an experimental design approach, namely conducting laboratory tests. The initial stage was to make swallow's nest extract by maceration technique using 96% ethanol solvent (the aim is to get anti-bacterial active substances, namely D-Galactose and Sialic acid contained in swallow's nest), the result of the extraction was a dry extract weighing 1.8195 grams which was then dissolved again using DMSO solution with concentrations of 10%, 20%, and 30%. The second stage is the swallow's nest extract test with the two test bacteria. The results of the swallow's nest extract test at concentrations of 10%, 20%, 30% against Streptococcus mutans and Porphyromonas gingivalis bacteria showed no inhibition. Future research could be further developed toward wound healing